Book Review of "Legislatures and the Budget Process: The Myth of Fiscal Control" - Stapenhurst, Rick (Taylor and Francis, 2013)
Are legislatures in control of budget processes or is fiscal control by legislatures a myth? Joachim Wehner addresses this and related questions in his new book on the role of the legislature in the budget decision-making process.